Affective capitalism: Investments and investigations - Tero Karppi; Lotta Kähkönen; Mona Mannevuo; Mari Pajala; Tanja Sihvonen (United Kingdom, 2022)
Affective capitalism is a mode of production where systems of organising production and distribution rely on the capacities of different bodies, human and non-human, to encounter each other. These encounters and different modes of capital that emerge are surrounded by a vast array of technologies of production, capture, valorisation, commodification and transformation. Affective capitalism appeals to our desires, it needs social relationships, and organises and establishes them.